The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1973
DOI: 10.1104/pp.52.3.263
|View full text |Cite
|
Sign up to set email alerts
|

Peroxidase Activity in the Abscission Zone of Bean Leaves during Abscission

Abstract: Peroxidase activity and localization in the abscission zone of bean leaves were studied histochemically and by gel electrophoresis. Deblading of bean leaves resulted in an increase in peroxidase activity in the abseission zone 2 to 4 days after deblading with highest activity just prior to separation. In debladed plants, the Peroxidase has been implicated in a number of diverse phenomena observed in plants (29,31,34,35) including the synthesis of ethylene (21,38). Similarly, conflicting reports (10,18) indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

1974
1974
2008
2008

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 26 publications
(27 reference statements)
1
8
0
Order By: Relevance
“…, 2003) from superoxide anion and hydrogen peroxide. Indeed, debalding bean leaves showed an increase in peroxidase (Poovaiah and Rasmussen, 1973), and in our system decapitated poinsettia flower pedicels also revealed peroxidase in the distal area (data not shown). Such peroxidases can produce high amounts of •OH, leading to pectic polysaccharide cleavage, and may be involved in cell wall alterations in the distal cells.…”
Section: Discussionmentioning
confidence: 47%
“…, 2003) from superoxide anion and hydrogen peroxide. Indeed, debalding bean leaves showed an increase in peroxidase (Poovaiah and Rasmussen, 1973), and in our system decapitated poinsettia flower pedicels also revealed peroxidase in the distal area (data not shown). Such peroxidases can produce high amounts of •OH, leading to pectic polysaccharide cleavage, and may be involved in cell wall alterations in the distal cells.…”
Section: Discussionmentioning
confidence: 47%
“…This effect coupled with an ethylenemediated auxin transport inhibition in the petiole quickly drops the concentration of the auxin at the abscission zone to a point where the cells in this region become responsive to the gas in terms of enzyme induction (2,23,34) and secretion (5), leading to leaf drop. All of these ethylene-mediated processes are readily reversible since the removal of ethylene at any time up to the time of actual cell separation halts the abscission process (9,17).…”
Section: Resultsmentioning
confidence: 99%
“…This is not too surprising since the localized application of potent auxin transport inhibitors to the petiole also does not trigger abscission in the absence of applied ethylene. Presumably, there is a lack of abscission under these conditions because there is insufficient ethylene at the abscission zone to trigger enzyme induction (2,23,34) and secretion (5). This view is supported by the observation that the sensitivity of leaves to ethylene is increased by pretreating only the leaf blade with ethylene.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Abscission also occurs in plants exposed to external stress such as darkness and dryness (REUVENI et al 1974). Increase of peroxidase activity was often found in plant tissue during infection of higher plants by pathogens (FARKAS and STAH-MANN 1966, MARAITE 1973, MAXWELL and BATEMAN 1967, SHAW and HAW-KINS 1958 and in the abscission zone fragment of non-infected bean plants during the abscission process (POOVAIAH and RASMUSSEN 1973). Recently, we have shown that the leaf abscission of infected pepper plants may be stimulated by external administration of Mn^ , a known co-factor for peroxidase activity, and diminished by indole-3-acetic acid (IAA) or its analog, indole-3butyric acid (IBA) (REUVENI et al 1976).…”
mentioning
confidence: 99%